Удмуртская народная кухня - Соковнин Герман Иванович (Удмуртия, 2020)
Экземпляры: ф.1 (20200917) / Инвентарный номер: 60282 / Цена: / Сис.шифр: 36.997(2Рос.Удм) / Авт.знак: С 59 / ГРНТИ: 65 / ББК: 36.997(2)